Rasa on screen (Mantichora. Italian Journal of Performance Studies, 2020)
By asking partakers to ingest, relish, internalize, and personalize the event, engaging partakers as co-creators of the event, focusing on affect, and creating dramaturgical structures that allow partakers to savor and digest, site-based digital productions are inherently rasic. When digital performances are analyzed in terms of rasa, they emerge as genres that fundamentally shift the aesthetic goals, dramaturgical structures, and modes of engagement in contemporary theatre.